Fluorine-containing sodium ion positive electrode material and preparation method thereof, sodium ion battery and electric equipment
By preparing the sodium fluorine-containing ion positive electrode material, the problems of structure collapse, slow sodium ion transfer and poor stability during the charging and discharge process of sodium ion battery positive electrode material are solved, and the performance of the material is improved and the service life is extended.
Patent Information
- Application Number
- CN202510022701.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-22
AI Technical Summary
The existing sodium ion battery positive electrode materials have problems such as structural collapse, slow sodium ion transfer kinetics and poor stability during charging and discharging, which limits the practical application of the material.
Using the preparation method of a positive electrode material containing sodium fluorine ion, a positive electrode material with a core-shell structure is prepared by mixing a nickel ferromanganese precursor, sodium carbonate and zinc oxide, adding fluoride and phosphate, and heat treatment is performed.
The sodium fluorine-containing ion positive electrode material synthesized by this method has excellent performance, better spherical structure, enhanced crystal structure bonds, improved sodium ion transport channels and improved structural stability, extending the service life of the material.
Smart Images

Figure CN119864357A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a fluorine-containing sodium ion positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art
[0002] Sodium-ion batteries have a similar working principle to lithium-ion batteries, and sodium resources are abundant and low in cost, so sodium-ion batteries are expected to become energy storage devices that can replace lithium-ion batteries. The positive electrode material in sodium-ion batteries, as a key component, plays a decisive role in the energy density and cycle life of the entire battery.
[0003] Among the sodium-ion battery cathode materials currently under study, layered transition metal oxide cathode materials have become a hot research system due to their high discharge specific capacity, simple preparation method and environmental friendliness. However, there are more or less some unavoidable problems in the actual charging and discharging process of the materials, such as structural collapse caused by the complex phase change process caused by the deintercalation of sodium ions with a larger radius, poor rate performance due to slow sodium ion transfer kinetics, and poor stability due to reactions with substances in the air, which is not conducive to storage and transportation. These problems limit the practical application of cathode materials.
[0004] Therefore, improving and solving the above problems through reasonable means to improve the performance of layered positive electrode materials is the key to the current development of sodium ion batteries. Summary of the invention
[0005] The purpose of the present application is to provide a fluorine-containing sodium ion positive electrode material and a preparation method thereof, a sodium ion battery and an electrical device to solve the above-mentioned problems.
[0006] To achieve the above objectives, the present application provides a first aspect of a method for preparing a fluorine-containing sodium ion positive electrode material, comprising:
[0007] Mixing nickel iron manganese precursor, sodium carbonate and zinc oxide to obtain material A;
[0008] The material A, fluoride and phosphate are mixed to obtain material B;
[0009] Material B is heat treated to obtain a fluorine-containing sodium ion positive electrode material.
[0010] Optionally, the molar ratio of the nickel-iron-manganese precursor, the sodium carbonate and the zinc oxide is 1.5-2.5:0.8-1.05:0.005-0.05.
[0011] Optionally, the mass ratio of the material A, the fluoride and the phosphate is 1:0.001-0.05:0.001-0.03.
[0012] Optionally, the method for preparing the fluorine-containing sodium ion positive electrode material satisfies at least one of the following conditions:
[0013] A. The fluoride includes one or more of lanthanum fluoride, yttrium fluoride, calcium fluoride, magnesium fluoride, cerium fluoride, zirconium fluoride, and aluminum fluoride;
[0014] B. The phosphate includes one or more of iron phosphate, aluminum phosphate, and magnesium phosphate.
[0015] Optionally, the fluoride comprises yttrium fluoride.
[0016] Optionally, the method for preparing the fluorine-containing sodium ion positive electrode material satisfies at least one of the following conditions:
[0017] A. The heating rate of the heat treatment is 2°C / min-5°C / min;
[0018] B. The heat treatment includes a first heat treatment with a gradient temperature increase, a second heat treatment and a third heat treatment;
[0019] The terminal temperature of the first heat treatment is 400°C-600°C, and the time is 1h-3h;
[0020] The end point heating temperature of the second heat treatment is 600°C-800°C, and the time is 3h-5h;
[0021] The terminal heating temperature of the third heat treatment is 900°C-950°C, and the time is 10h-15h.
[0022] Optionally, before the heat treatment, the material B is ground, and the grinding satisfies at least one of the following conditions:
[0023] A. The grinding comprises ball milling;
[0024] B. The grinding time is 2h-8h;
[0025] C. The grinding speed is 100r / min-800r / min.
[0026] The second aspect of the present application provides a fluorine-containing sodium ion positive electrode material, which is prepared by the preparation method of the fluorine-containing sodium ion positive electrode material.
[0027] The third aspect of the present application provides a sodium ion battery, comprising the fluorine-containing sodium ion positive electrode material.
[0028] A fourth aspect of the present application provides an electrical device, comprising the sodium ion battery.
[0029] Compared with the prior art, the beneficial effects of this application include:
[0030] The present application provides a method for preparing a fluorine-containing sodium ion positive electrode material. The fluorine-containing sodium ion positive electrode material synthesized by the synthesis method has excellent performance, and only requires one sintering to synthesize the target material. The synthesis process is simple, energy-saving and consumption-reducing, and is more conducive to industrial production.
[0031] The fluorine-containing sodium ion positive electrode material provided in the present application is a core-shell structure, presenting a better spherical shape, wherein the core is a sodium nickel iron manganate ternary positive electrode material doped with zinc, fluorine and phosphoric acid, and the shell is a physical barrier layer uniformly coated with fluoride and phosphate, which prevents the electrode material from directly contacting the electrolyte and causing side reactions with the electrolyte to cause the electrode material to collapse in structure. In addition, the doping of F ions with strong electronegativity enhances the bond strength in the crystal structure, increases the sodium layer spacing, and provides a fast transmission channel for the deintercalation of sodium ions, thereby alleviating the downward trend of the discharge platform voltage during the material cycle and improving the structural stability; and zinc oxide doping can improve the electronic conductivity and ion diffusion rate of the material, thereby improving the specific capacity of the material.
[0032] The sodium ion battery and electrical equipment provided in this application have long service life and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0034] Figure 1 This is a SEM image of the fluorine-containing sodium ion positive electrode material provided in Example 1;
[0035] Figure 2 This is a SEM image of the fluorine-containing sodium ion positive electrode material provided in Comparative Example 5;
[0036] Figure 3 The graphs are the cycle performance test graphs of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5;
[0037] Figure 4 It is a rate performance test curve diagram of Example 1 and Comparative Example 5. DETAILED DESCRIPTION
[0038] As used herein:
[0039] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0040] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0041] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0042] In these examples, parts and percentages are by mass unless otherwise indicated.
[0043] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0044] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0045] The first aspect of the present application provides a method for preparing a fluorine-containing sodium ion positive electrode material, comprising:
[0046] Mixing nickel iron manganese precursor, sodium carbonate and zinc oxide to obtain material A;
[0047] The material A, fluoride and phosphate are mixed to obtain material B;
[0048] Material B is heat treated to obtain a fluorine-containing sodium ion positive electrode material.
[0049] In some embodiments, the chemical formula of the nickel iron manganese precursor is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.
[0050] In some embodiments, the molar ratio of the nickel-iron-manganese precursor, the sodium carbonate, and the zinc oxide is 1.5-2.5: 0.8-1.05: 0.005-0.05.
[0051] Optionally, the molar ratio of nickel iron manganese precursor, sodium carbonate and zinc oxide can be 1.5:0.8:0.005, 2:0.8:0.005, 2.5:0.8:0.005, 1.5:0.9:0.005, 1.5:1:0.005, 1.5:1.05:0.005, 1.5:0.8:0.05, 2.5:1:0.05 or any value between 1.5-2.5:0.8-1.05:0.005-0.05.
[0052] It should be noted that when the molar ratio of nickel iron manganese precursor, sodium carbonate and zinc oxide is 1.5-2.5:0.8-1.05:0.005-0.05, the synthesized material has a higher specific capacity and better cycle stability. Compared with the analysis of Comparative Example 8, the addition of a small amount of zinc oxide can improve the electronic conductivity and ion diffusion rate of the material, thereby improving the specific capacity of the material.
[0053] In some embodiments, the mass ratio of the material A, the fluoride, and the phosphate is 1:0.001-0.05:0.001-0.03.
[0054] Optionally, the mass ratio of material A, fluoride and phosphate can be 1:0.001:0.001, 1:0.01:0.001, 1:0.02:0.001, 1:0.03:0.001, 1:0.04:0.001, 1:0.05:0.001, 1:0.001:0.01, 1:0.001:0.02, 1:0.001:0.03 or any value between 1:0.001-0.05:0.001-0.03.
[0055] It should be noted that when the mass ratio of material A, fluoride, and phosphate is 1:0.01:0.01, the synthesized material is superior in both specific capacity and cycle stability.
[0056] In some embodiments, the method for preparing the fluorine-containing sodium ion positive electrode material satisfies at least one of the following conditions:
[0057] A. The fluoride includes one or more of lanthanum fluoride, yttrium fluoride, calcium fluoride, magnesium fluoride, cerium fluoride, zirconium fluoride, and aluminum fluoride;
[0058] It should be noted that the selected fluorides are all common fluorides, and the materials are cheap, and high-temperature heat treatment does not produce harmful gases and does not pollute the environment;
[0059] In some embodiments, the fluoride comprises yttrium fluoride;
[0060] It should be noted that the yttrium element in yttrium fluoride combines with the oxygen in the material to form a YO bond, which can stabilize the crystal structure of the material, inhibit the slip of the transition metal, and prevent the occurrence of irreversible phase change. 3+ Substitution also reduces the Mn content in the material to a certain extent. 3+ / Mn 4+ The ratio of 2.5% to 1.5% can reduce the Jiang-Taylor effect and improve the cyclic stability of the material;
[0061] B. The phosphate includes one or more of iron phosphate, aluminum phosphate, and magnesium phosphate.
[0062] It should be noted that the selected phosphates are all common phosphates, the materials are cheap, high-temperature heat treatment does not produce harmful gases, and does not pollute the environment.
[0063] In some embodiments, the yttrium atoms in yttrium fluoride combine with the oxygen atoms in the material to form YO bonds to stabilize the crystal structure and prevent the occurrence of irreversible phase changes; secondly, iron phosphate and yttrium fluoride are co-doped to in situ construct a derivative YPO4-Na3PO4 phospholipid layer on the surface of the material, which can enhance the transmission of sodium ions, and YPO4 relieves the stress during the cycle. The YPO4-Na3PO4 phospholipid layer can also selectively pass sodium ions and consume residual sodium compounds on the surface of the material, thereby alleviating the stress during the cycle. It can selectively pass sodium ions and consume residual sodium compounds on the surface of the material, thereby greatly inhibiting interfacial side reactions and improving the cyclic stability of the material.
[0064] In some embodiments, the method for preparing the fluorine-containing sodium ion positive electrode material satisfies at least one of the following conditions:
[0065] A. The heating rate of the heat treatment is 2°C / min-5°C / min;
[0066] Optionally, the heating rate of the heat treatment may be 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any value between 2°C / min and 5°C / min;
[0067] B. The heat treatment includes a first heat treatment with a gradient temperature increase, a second heat treatment and a third heat treatment;
[0068] The terminal temperature of the first heat treatment is 400°C-600°C, and the time is 1h-3h;
[0069] Optionally, the terminal heating temperature of the first heat treatment may be 400°C, 500°C, 600°C or any value between 400°C and 600°C, and the time may be 1h, 2h, 3h or any value between 1h and 3h;
[0070] The end point heating temperature of the second heat treatment is 600°C-800°C, and the time is 3h-5h;
[0071] Optionally, the end point heating temperature of the second heat treatment may be 600°C, 650°C, 700°C, 750°C, 800°C or any value between 600°C and 800°C, and the time may be 3h, 4h, 5h or any value between 3h and 5h;
[0072] The terminal heating temperature of the third heat treatment is 900°C-950°C, and the time is 10h-15h.
[0073] Optionally, the terminal heating temperature of the third heat treatment can be 900°C, 925°C, 950°C or any value between 900°C and 950°C, and the time can be 10h, 11h, 12h, 13h, 14h, 15h or any value between 10h and 15h.
[0074] It should be noted that the first heat treatment, the second heat treatment and the third heat treatment with gradient temperature increase are set. The first gradient heat treatment is to pre-burn the material, and its purpose is to remove the natural water and crystal water in the material; the second gradient heat treatment allows the sodium carbonate and nickel iron manganese precursors with low melting points to react and preliminarily generate the core structure of the target material. The purpose of setting this temperature is to prevent the formation of oxygen-deficient compounds due to excessively high temperature, and the material grains will not become larger. The original spherical structure of the precursor will not be destroyed due to excessively rapid reaction, which is more conducive to the removal and embedding of sodium ions; the third gradient heat treatment stage is the solid phase reaction stage, and the final high-temperature heat treatment reaction generates the corresponding positive electrode material, and the phosphates and fluorides with higher decomposition temperatures are decomposed and evenly coated on the surface of the material, forming a uniform protective layer (shell) on the surface of the target material, thereby improving the cycle stability of the material.
[0075] In some embodiments, iron phosphate and yttrium fluoride with higher decomposition temperatures are simultaneously decomposed and uniformly coated on the surface of the material, forming a uniform protective layer (shell) on the surface of the target material, thereby improving the cyclic stability of the material.
[0076] In some embodiments, before the heat treatment, the material B is further ground, and the grinding satisfies at least one of the following conditions:
[0077] A. The grinding comprises ball milling;
[0078] B. The grinding time is 2h-8h;
[0079] Optionally, the grinding time can be 2h, 3h, 4h, 5h, 6h, 7h, 8h or any value between 2h and 8h;
[0080] C. The grinding speed is 100r / min-800r / min.
[0081] Optionally, the grinding rotation speed can be 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min, 800r / min or any value between 100r / min-800r / min.
[0082] The second aspect of the present application provides a fluorine-containing sodium ion positive electrode material, which is prepared by the preparation method of the fluorine-containing sodium ion positive electrode material.
[0083] The third aspect of the present application provides a sodium ion battery, comprising the fluorine-containing sodium ion positive electrode material.
[0084] A fourth aspect of the present application provides an electrical device, comprising the sodium ion battery.
[0085] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0086] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0087] The melting points of the sodium carbonate, nickel iron manganese precursor, fluoride and phosphate used in the examples and comparative examples are shown in Table 1.
[0088] Table 1 Melting points of various compounds
[0089] Material Melting point / ℃ Anhydrous sodium carbonate 851 Nickel Iron Manganese Precursor 1234 Zinc Oxide 1975 Yttrium fluoride 1387 Lanthanum fluoride 1493 Calcium Fluoride 1402 Aluminum fluoride 1040 Iron phosphate 1000 Aluminum phosphate 1500 Magnesium phosphate 1184
[0090] Example 1
[0091] This embodiment provides a fluorine-containing sodium ion positive electrode material and a preparation method thereof, and the specific steps are as follows:
[0092] S1: Weigh a certain amount of nickel iron manganese precursor (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2), anhydrous sodium carbonate, zinc oxide to obtain material A;
[0093] S2: Weigh material A, yttrium fluoride and iron phosphate in a mass ratio of 1:0.01:0.01, and mix to obtain material B;
[0094] S3: Material B is placed in a ball mill for ball milling at a speed of 500 r / min and a ball milling time of 5 h. The ball-milled material is transferred into a crucible and heat-treated in a box-type muffle furnace at a heating rate of 5 °C / min. The heat treatment process comprises three gradient temperatures, namely 550 °C / 3 h, 750 °C / 5 h, and 920 °C / 12 h, with a heating rate of 5 °C / min. After naturally cooling to room temperature, a fluorine-containing sodium ion positive electrode material is obtained.
[0095] The scanning electron microscopy of the fluorine-containing sodium ion positive electrode material is shown in Figure 1 shown.
[0096] This embodiment also provides a sodium ion battery, wherein the slurry is stirred at a mass ratio of positive electrode material: conductive agent: binder of 80:10:10, and NMP is used as a solvent to prepare a positive electrode slurry, the prepared positive electrode slurry is uniformly coated on an aluminum foil, dried in a vacuum drying oven at 120° C. for more than 12 hours, and then cut into discs with a diameter of 16 mm, and assembled into CR2025 sodium ion button batteries in a glove box filled with argon gas, and the electrolyte is 1M NaClO4 PC 5% FEC;
[0097] Example 2
[0098] The difference from Example 1 is that the mass ratio of material A, yttrium fluoride and iron phosphate is 1:0.02:0.015.
[0099] Example 3
[0100] The difference from Example 1 is that yttrium fluoride is replaced by lanthanum fluoride.
[0101] Example 4
[0102] The difference from Example 1 is that yttrium fluoride is replaced by calcium fluoride.
[0103] Example 5
[0104] The difference from Example 1 is that yttrium fluoride is replaced by aluminum fluoride.
[0105] Comparative Example 1
[0106] The difference from Example 1 is that no fluoride and phosphate are added.
[0107] Comparative Example 2
[0108] The difference from Example 1 is that yttrium fluoride is not added.
[0109] Comparative Example 3
[0110] The difference from Example 1 is that iron phosphate is replaced by aluminum phosphate.
[0111] Comparative Example 4
[0112] The difference from Example 1 is that the iron phosphate is replaced by magnesium phosphate.
[0113] Comparative Example 5
[0114] The difference from Example 1 is that no gradient heating treatment is performed, and the heating rate is directly 5° C. / min, the terminal heating temperature is 920° C., and the treatment is carried out for 15 hours.
[0115] The scanning electron microscopy of the fluorine-containing sodium ion positive electrode material is shown in Figure 2 shown.
[0116] Comparative Example 6
[0117] The difference from Comparative Example 2 is that no gradient heating treatment is performed, and the heating rate is directly 5°C / min, the terminal heating temperature is 920°C, and the treatment is carried out for 15h.
[0118] Comparative Example 7
[0119] The difference from Example 1 is that no phosphate is added.
[0120] Comparative Example 8
[0121] The difference from Example 1 is that zinc oxide is not doped.
[0122] Among them, the cycle performance test curves of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5 are as follows: Figure 3 As shown, the rate performance test curves of Example 1 and Comparative Example 5 are as follows Figure 4 shown.
[0123] The sodium ion batteries prepared in the above Examples 1-5 and Comparative Examples 1-8 were subjected to electrochemical performance tests (1C = 140 mA / g). After three cycles at 2V-4.0V and 0.1C rate, long cycle tests were performed at 1C rate. The specific test results are shown in Table 2.
[0124] Table 2 Electrochemical performance
[0125]
[0126]
[0127] analyze:
[0128] As can be seen from Table 1, combined with the analysis and comparison of Example 1 and Example 2, it is found that increasing the doping amount of yttrium fluoride and iron phosphate in Example 2 can improve the cycle stability of the material to a certain extent, but its specific capacity decreases significantly, sacrificing the specific capacity of the material. The reason is that the shell structure formed on the surface of the material by adding too much coating agent is too thick, which hinders the transmission of sodium ions, thereby reducing the specific capacity of the material. Example 1 and Example 2 are subjected to gradient temperature heat treatment and doped with a certain amount of yttrium fluoride and iron phosphate. The material has obvious improvements in specific capacity, cycle stability and rate performance.
[0129] In Examples 3, 4, and 5, lanthanum fluoride, calcium fluoride, and aluminum fluoride are used to replace yttrium fluoride, and the overall performance of the synthesized materials is improved, with certain beneficial effects, but they are slightly worse than Example 1. This is because of the beneficial effect of the yttrium element in yttrium fluoride. The yttrium element combines with O in the material to form a YO bond, which can stabilize the crystal structure of the material, inhibit the slip of transition metals, prevent the occurrence of irreversible phase changes, and improve the overall performance of the material.
[0130] Comparative Example 1 is not doped with yttrium fluoride and iron phosphate, and its cycle stability and rate performance are poor; while Comparative Example 2 and Comparative Example 7 are only doped with fluoride or phosphate alone and cannot achieve the effect of "iron phosphate and yttrium fluoride are co-doped to in situ construct a layer of derived YPO4-Na3PO4-type phospholipid layer on the surface of the material, which can enhance the transmission of sodium ions, and YPO4 relieves the stress during the cycle, and the YPO4-Na3PO4-type phospholipid layer can also selectively pass sodium ions and consume residual sodium compounds on the surface of the material, relieve the stress during the cycle, and it can selectively pass sodium ions and consume residual sodium compounds on the surface of the material"; Comparative Examples 5 and 6 are only sintered at a single temperature, and the obtained material performance is poor, because the single temperature sintering destroys the original spherical morphology of the material, and the material is converted from the original polycrystalline to a single crystal; Comparative Example 8 is not doped with zinc oxide, and the synthesized material has a low specific capacity, because the addition of a small amount of zinc oxide can improve the electronic conductivity and ion diffusion rate of the material, thereby improving the specific capacity of the material.
[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0132] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a fluorine-containing sodium ion positive electrode material, characterized in that: include: Mixing nickel iron manganese precursor, sodium carbonate and zinc oxide to obtain material A; The material A, fluoride and phosphate are mixed to obtain material B; Material B is heat treated to obtain a fluorine-containing sodium ion positive electrode material.
2. The method for preparing a fluorine-containing sodium ion positive electrode material according to claim 1, characterized in that: The molar ratio of the nickel-iron-manganese precursor, the sodium carbonate and the zinc oxide is 1.5-2.5:0.8-1.05:0.005-0.
05.
3. The method for preparing a fluorine-containing sodium ion positive electrode material according to claim 1, characterized in that: The mass ratio of the material A, the fluoride and the phosphate is 1:0.001-0.05:0.001-0.
03.
4. The method for preparing a fluorine-containing sodium ion positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. The fluoride includes one or more of lanthanum fluoride, yttrium fluoride, calcium fluoride, magnesium fluoride, cerium fluoride, zirconium fluoride, and aluminum fluoride; B. The phosphate includes one or more of iron phosphate, aluminum phosphate, and magnesium phosphate.
5. The method for preparing a fluorine-containing sodium ion positive electrode material according to claim 4, characterized in that: The fluoride includes yttrium fluoride.
6. The method for preparing a fluorine-containing sodium ion positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. The heating rate of the heat treatment is 2°C / min-5°C / min; B. The heat treatment includes a first heat treatment with a gradient temperature increase, a second heat treatment and a third heat treatment; The terminal temperature of the first heat treatment is 400°C-600°C, and the time is 1h-3h; The end point heating temperature of the second heat treatment is 600°C-800°C, and the time is 3h-5h; The terminal heating temperature of the third heat treatment is 900°C-950°C, and the time is 10h-15h.
7. The method for preparing a fluorine-containing sodium ion positive electrode material according to any one of claims 1 to 6, characterized in that: Before the heat treatment, the material B is ground, and the grinding satisfies at least one of the following conditions: A. The grinding comprises ball milling; B. The grinding time is 2h-8h; C. The grinding speed is 100r / min-800r / min.
8. A fluorine-containing sodium ion positive electrode material, characterized in that: The fluorine-containing sodium ion positive electrode material is prepared by the preparation method of any one of claims 1 to 7.
9. A sodium ion battery, characterized in that: Including the fluorine-containing sodium ion positive electrode material as described in claim 8.
10. An electrical device, characterized in that: Including the sodium ion battery as described in claim 9.